The Global Economic Crisis-What Should NOT be Forgotten - Trenovski, Borce; Tashevska, Biljana; Makreshanska mladenovska, Suzana (Center for Economic Analyses, 2015)
The global economic crisis opened a new chapter in economic policy and awakened economic science. Its severity, the various negative financial and economic shocks and the impotence of the economic policy response revealed new questions about the background and the causes of the economic crisis – what led to the emergence of the global economic crisis, are the causes new or already known, are there similarities with previous crises? The great number of analyses regarding these questions reveals different aspects that complete the whole picture of the causes, factors and lessons about the crisis that need to be remembered. This paper tries to offer an analysis of the causes and factors that contributed to the global economic distress by analyzing the global economic events that accumulated in the pre-crisis period. The main purpose is to synthesize and define the key direct and indirect economic events and developments that need to be considered by economic science and policy and that must not be forgotten in further analyses of the global economic development in the future.
Keywords: global economic crisis, financial system, global economic imbalances, real estate bubble